Mario Sergio Cortella e o artigo 205 da Constituição da República Federativa do Brasil de 1988: reflexões sobre o dever familiar de educar - Oliveira, Nicollas Madeira de (2021)
The present dissertation - with the support of some of the great masters of thought, dedicated to the present theme - seeks to analyze and promote an examination of the family duty to educate based on the reflections of Mario Sergio Cortella. Prior to the State and its entry into the schooling process - a fundamental process, but only part of the educational process - there is no family nucleus that the human being has his first experience of living, sharing, and society. The Constitution of the Republic in the norm of its article 205 records the family duty to educate. However, although it manifests itself in terms of effecting the duty of the State, it does not concern family duty and its effectiveness falls silent. And when dealing with education, about the preparation of the human being for a harmonious, honest and ethical coexistence with others, about the preparation of each human being for the fullest development of his faculties, knowledge of his powers, knowledge of his inherent dignity , silence cannot have space, omission cannot find a place, consequently falling all this responsibility, but also privilege, on the small and first group, the family group